R PENGARUH PENGGUNAAN MEDIA DIGITAL WORDWALL PADA PEMBELAJARAN MATEMATIKA TERHADAP MINAT BELAJAR SISWA KELAS IV SDN 10 SIAK KECIL - Risnawati; Jesi Alexander Alim; Zetra Hainul Putra; Rena (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Student learning interest in mathematics is still low due to the implementation of monotonous learning models resulting in a lack of use of interactive learning media. Therefore, this study aims to determine the effect of the use of digital media wordwalls on student learning interest in mathematics learning in grade IV of SDN 10 Siak Kecil. This study used a pre-experimental design method with a